Empowering Workers and Labor NGOs in China: Creating a Law Searching Tool through a Design Science Approach - Hu, Fumin (2018)
Labor NGOs in China has been utilizing various social media tools, such as WeChat for networking workers and promotion. In the year 2017 WeChat Mini Program was released, allowing developers to create “sub-application” within WeChat. This research evolves from a laws-searching WeChat Mini Program development project, which will adopt a design science approach, follow the design science research methodology (DSRM) process model, and measure the effect of this tool with the concepts from information systems success model and post-adoption behaviors, as well as empowerment and affordance. Usage data and user feedback of this tool were positive, providing it a successful at-tempt of utilizing new tools for labor NGOs.